A recepção de rádio e televisão por jovens do movimento dos atingidos por barragens: as representações da classe popular - Rossato, Alexania (2008)
This work aims to present theoretic-conceptual elements and empirical evidences in order to better comprehend the radio and television reception processes by young farmers through the following mediation categories: daily life and social movement, both structured and determined by the social class and culture. This comprehension is achieved through the sample of the population studied, composed of young activists of the Movement of Dam Affected People (MAB), and by the context of the research scenario: the Municipality Anita Garibaldi in the State of Santa Catarina, in the hydrographical basin of the Uruguai River, on the frontier between the states Rio Grande do Sul and Santa Catarina, where the Hydroelectric Power Plant of Barra Grande was constructed. This focus seeks to clarify the manner in which hegemony works and the dispute for the popular in an environment where radio and television representations of wealth and poverty, rural and urban, past and modern, MAB and the BAESA consortium, are accepted, denied or negotiated by the social actors. The theoreticalmethodological framework that structures this work, is based on Latin American studies on reception and on an ethnographic approach, adopted as the method that allows the researcher to be introduced into the world of the interviewed, evaluating with higher precision the elements composing the reception process. The research procedures, instruments and techniques utilized for the elaboration of the study were: semi-structured interviews, secondary material collection and participation in educational activities of MAB. In addition to these techniques, all observations were registered in a fieldwork log book. This study is divided into four chapters which deal with the following issues: the theoretical communication framework, the cultural factors constituting the determination of reception, the aspects linked to the organization of social movements and in particular of MAB, the organization context in the region analysed and finally the knowledge empirically founded on the description and analysis of reception practices. The main results from the analysis of the empirical data point to the fact that the mediation of the quotidian, both conditions and is conditioned by the participation of the social movement; the consciousness of the condition of subalternity leads to the prioritisation of opposite readings of radio and television contents and furthermore, the appreciation of the rural culture is achieved through insertion in the social movement and it is this appreciation that allows comprehension of the social system and its transformation.